Serbia and Montenegro : Republic of Montenegro, Economic Memorandum, A Policy for Growth and Competitiveness - World Bank (Washington, DC, 2012)
Beginning in the late 1990s, Montenegro's economic reform program reached momentum in the early 2000s. Its reform program rested on two broad pillars: macroeconomic stabilization, and market-oriented structural reforms. However, the macroeconomic and structural reforms have yielded modest economic recovery and transition, holding a current account deficit, which although still high, is improving; yet its principal human welfare indicators such as poverty, life expectancy, and adult literacy remained moderate and stable. But significant challenges remain. Three key challenges confront policy makers in Montenegro. First, past economic growth has been inadequate. Second, the limited growth recovery has not been accompanied by employment growth. Third, despite reforms, Montenegro has become less competitive over the last four years: its real exchange rate, based on movements in unit labor costs, has risen much faster than that of the European Union (EU) zone and the United States. Therefore, recommendations suggest key labor market reforms need to be undertaken to increase employment, growth, and competitiveness, through specific measures to: control the rapid wage growth witnessed in recent years; relax some aspects of the labor regulations; and, reduce the high rates of labor taxation, in a fiscally responsible way to encourage formal employment. Enterprise privatization and restructuring needs to: speed up the restructuring of the mass-voucher- privatized companies, and, speed up the consolidation into majority shares of the companies' shares being traded on stock exchanges. Furthermore, key constraints facing the emerging private sector, including businesses in the informal sector, must be removed, reducing specific governance and regulatory bottlenecks, and the backlog of commercial court cases, to speed up contract enforcement; while in addition, land title transparency and property rights must be improved. The cost of capital needs to be reduced, and financial intermediation improved, while employment creation, growth, and competitiveness should be increased through Government's help, by undertaking fiscal reforms. Finally, tourism holds considerable promise for Montenegro's export-oriented growth, and employment creation.